The Identification of Physical-Chemical Properties to Detect Bacterial Contamination in Chicken Meat from Local Markets in Kendari, Southeast Sulawesi, Indonesia - Yamin Yaddi; Ida Usman; Deki Zulkarnain; Achmad Selamet Aku; La Ode Sahaba; La Ode Muh. Munadi; Restu Libriani; Fitrianingsih Fitrianingsih (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
The absence of microbial contamination is one requirement for the viability of using chicken meat as a feed ingredient. Many microbes that are implicated as food pollutants come from bacterial families. This study aimed to identify and characterize contaminating bacteria in chicken meat processed at the local market's chicken slaughterhouse in Kendari. In this study, both descriptive and experimental methods were applied. Differentially selective mediums for Gram-negative bacteria were used for bacterial isolation. Bacteria were identified using the Eosin methylene blue agar (EMBA) medium, which can ferment lactose and sucrose. The presence of bacteria was confirmed macroscopically using biochemical characteristics and microscopically using Gram stain staining. The ability of bacteria to ferment glucose, sucrose, and lactose and their ability to produce gas and H2S were identified based on their physicalchemical properties through the Triple Sugar Iron Agar (TSIA) test. The results showed that 96% of the examined samples were microbially contaminated. The various types of infecting bacteria included 52% of Pseudomonas sp., 68% of Salmonella sp., and 36% of Escherichia coli. Poor hygiene practices are the main cause of contamination in chicken meat during production. The local market in Kendari sells chicken meat that does not fulfill food safety criteria, especially given bacterial infection.